Effect of volume concentration and nanofluid temperature on whe thermal conductivity of mono and hybrid Al2O3-TiO2 nanofluid - Vicki W.V.; Abdullah M.Z.; Gunnasegaran P. (American Institute of Physics Inc., 2023)
This study investigated the effect of Al2O3-TiO2 nanoparticle volume concentration and nanofluid temperature on the thermal conductivity of water-based mono and hybrid nanofluid. Aluminium oxide (Al2O3) and titanium oxide (TiO2) nanoparticles were characterised using the X-ray diffraction (XRD) method. The stable suspension of Al2O3-TiO2 hybrid nanofluids was prepared using various volume concentrations, ranging from 0.5% to 2.0%. The ratio of Al2O3-TiO2 nanoparticles was fixed at a constant ratio of 50:50 for all the experiments performed in this study. For the mono nanofluid, the volume concentration was fixed at 0.5 %. The thermal conductivity measurement for both mono and hybrid nanofluid was performed at a temperature range of 35C to 55. The crystallite sizes of Al2O3 and TiO2 nanoparticles calculated based on the XRD results measured approximately 12 nm and 20 nm, respectively. The results indicated that the increase in both the nanoparticle volume concentration and temperature contributed to the overall enhancement of thermal conductivity for hybrid nanofluids. The maximum thermal conductivity enhancement for hybrid nanofluid is significantly higher than the thermal conductivity enhancement for the Al2O3 andTiO2 mono nanofluid. 2021 American Institute of Physics Inc.. All rights reserved.